2015
DOI: 10.1149/2.0471514jes
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Characterization of Catalyst Coated Membranes Subjected to In Situ Hygrothermal Fatigue

Abstract: Catalyst coated membranes (CCMs) in polymer electrolyte fuel cells are subjected to mechanical stresses in the form of fatigue and creep that deteriorate the durability and lifetime of the cells. The present article aims to determine the effect of in-situ hygrothermal fatigue on the microstructure and mechanical properties of the CCM. The fatigue process is systematically explored by the application of two custom-developed accelerated mechanical stress test (AMST) experiments with periodic extraction of partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…For a fresh MEA, these features could be formed during manufacturing or be a consequence of poor handling, bending, or stretching of the MEA. Membrane expansion and contraction during fuel cell operation may also result in catalyst layer cracks [45,51,53]. Delamination, which is observed when the catalyst layer is separated from the membrane, may also occur during the manufacturing processes or during operation [45,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a fresh MEA, these features could be formed during manufacturing or be a consequence of poor handling, bending, or stretching of the MEA. Membrane expansion and contraction during fuel cell operation may also result in catalyst layer cracks [45,51,53]. Delamination, which is observed when the catalyst layer is separated from the membrane, may also occur during the manufacturing processes or during operation [45,51].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane expansion and contraction during fuel cell operation may also result in catalyst layer cracks [45,51,53]. Delamination, which is observed when the catalyst layer is separated from the membrane, may also occur during the manufacturing processes or during operation [45,51]. As discussed by Kundu et al [53], the high temperature applied in the catalyst layer drying stage can cause vapor to form at the catalyst layer/membrane interface, and create areas of poor adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…As the core component of PEFC, the performance and structural integrity of proton exchange membrane (PEM) are critical to the life of fuel cells. Perfluorosulfonic acid (PFSA) ionomer membranes (e.g., Nafion from DuPont) have been widely used and studied due to their outstanding performance 3 . During practical operation of fuel cells, PEMs will periodically swell and shrink due to water absorption and dehydration, resulting in mechanical fatigue 4 .…”
Section: Introductionmentioning
confidence: 99%
“…So it seems that there is no consensus on the effect of catalyst layer on fatigue life of fuel cell membranes. To further explore the cause of fatigue failure of CCM, Kjeang et al studied the mechanical degradation of membranes in fuel cells through accelerated stress tests (ASTs) and 4D visualization technology 3,36–38 . It was found that membrane–catalyst layer delamination and catalyst layer cracks led to the failure of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the CCM-MEA has been intensively studied for PEM fuel cells (PEMFC) [32][33][34][35][36][37][38][39][40][41], direct methanol fuel cells (DMFC) [42][43][44] and PEM electrolysers [44][45][46][47][48][49] to advantage, there is a lack of similar investigations for an alkaline environment due to the absence of an appropriate anion-selective polymer binder. To our knowledge, the only study evaluating the performance CCM-MEAs is that of Leng et al, who coated the surfaces of a commercial A201 membrane (Tokuyama Corp., Japan) with IrO2 catalytic ink (loading: 2.9 mg/cm 2 ) and Pt catalytic ink (loading: 3.2 mg/cm 2 ), using AS-4 ionomer (Tokuyama Corp., Japan) as a binder on the anode and cathode sides, respectively [50].…”
Section: Introductionmentioning
confidence: 99%